Substituted Methoxybenzene derivatives: C8H9NO4, C9H11NO5 and C13H18O4 - Fun, H.-K.; Chinnakali, K.; Sivakumar, K.; Sam, T.-W.; How, Siew Eng (1997)
The structures of three methoxybenzenes, namely 1,2-dimethoxy-4-nitrobenzene, C8H9NO4, (I), 1,2,3-trimethoxy-5-nitrobenzene, C9H11NO5, (II), and 1-(2,4,5-trimethoxyphenyl)-1-butanone, C13H18O4, (III), are reported. Molecules of (I) and (III) are planar, but one of the three methoxy groups of (II) is twisted out of the phenyl ring plane as a result of steric hindrance. In all three solids, the molecules are linked to form centrosymmetrically hydrogen-bonded dimers; they are packed in parallel layers in (I) and (II), but in zigzag layers in (III).